Agonistic trials with mirrors do not elicit the same aggressiveness of a real trial in the matrinxã fish, Brycon amazonicus (Spix & Agassiz, 1829) - Serra, M. [UNESP]; Wolkers, C. P.B. [UNESP]; Mello, M. M.M. [UNESP]; Urbinati, E. C. [UNESP] (Hindawi, 2017)
This study tested the efficacy of mirror trials in studying aggressiveness in the matrinxã fish, Brycon amazonicus. The hypothesis was that a mirror would elicit an aggressive response in B. amazonicus juveniles, but show different behavioral and physiological profiles than those observed in trials with real opponents. Fish were tested using either a mirror trial (n = 7) or a real trial (n = 7), that is, placed alone with a mirror or paired with a same-sized opponent, respectively. All trials lasted for 20 min and took place in 96-L aquaria with water temperatures of 28°C. Fish in mirror trials exhibited less locomotion (mirror: 423.3 ± 39.1; real trial: 735.1 ± 31.9; p <.001), rushed less against the opponent (mirror: 3.1 ± 2.3; real trial: 39.6 ± 5.1; p <.001) and showed less escalation of aggressive behavior compared to the winner of a real trial. Regarding the physiological parameters, despite similar cortisol responses (mirror: 84.2 ± 13.8 ng/ml; real trial: 77.2 ± 16.9 ng/ml; p =.757), the fish that fought against a mirror had lower levels of plasma glucose than those of fish that fought against a real opponent (mirror: 76.8 ± 3.6 ng/dl; real trial: 103.8 ± 10.1 ng/ml; p =.037). This lower energy mobilization might be due to a lower cost of the fight in the absence of an opponent that flees from attacks, as the locomotion and number of rush totals were also lower in the mirror trials. This pattern of less locomotion is probably common in mirror trials because the opponent is always limited to one side of the arena. If the energetic cost is one of the factors that can determine the outcome of a fight, and if mirror trials do not evoke the physiological response observed in a real fight, the use of mirror trials must be reviewed in studies that consider the physiological responses.